Comparing Malaysian and Scottish firms on practices for strategic capability management - Kanapathy, K.; Dekkers, R. (2014)
The study of practices for Strategic Capacity Management at five Malaysian companies and four Scottish companies shows that the Malaysian manufacturing managers acted more reactive due to pressures by sales and processing orders, whereas the Scottish managers were implementing a manufacturing strategy more 'independently'. Problems with suppliers, albeit sometimes caused by outsourcing, feature high on the list of challenges in both samples. Alignment of organisational structures and investment in technologies are seen by all as key to aligning the manufacturing strategy with the competitive strategy, though actual investments tend to be happening more in Scottish companies.